Reprint. From: portfolio "Revolučný Odkaz Slovenského Národného Povstania v politickom plagáte" - Pepich, Alojz, (1962)
Reprint. From: portfolio "Revolučný Odkaz Slovenského Národného Povstania v politickom plagáte".